The nurse’s role in a patient with phantom sensation- phantom pain - KATRAN, HAMDİYE BANU (My University, 2022)
The aim of this compilation is to review the role of the nurse in the patient who describes phantom sensationand phantom pain in the light of the literature. The problems that occur in individuals following operationssuch as amputation and mastectomy, which require removal of an organ / limb from the body, lead to disabilityin daily life activities in different dimensions, causing individuals to become fully or semi-dependent physically, economically and socially. The pain in the extremity, which is removed from the body after amputation,is called phantom pain and its mechanism is not fully understood yet. It is known that both peripheral andcentral nervous system play a role in phantom pain. Phantom Sensation (PS), which is defined as feeling thatthe limb or organ is still in place, and Phantom Pain (PP), seen as pain in the non-organ / limb, are commonchronic problems in the postoperative period. These symptoms, which prolong the healing process in patientsundergoing surgery, can only be identified by a comprehensive / complex assessment, and therefore the role ofthe nurse in management is large. In this compilation, we aimed to review the role of nurses in the treatmentand care of patients with phantom sensation and phantom pain
Keywords: Hemşirelik; Cerrahi Hastalıkları Hemşireliği; Sağlık Bilimleri; Nursing; Surgical Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing